A case of symmetrical drug-related intertriginous and flexural exanthema (Journal of Medical Science, 2022)
Symmetrical drug-related intertriginous and flexural exanthema (also known as Baboon syndrome) is a skin eruption in the intertriginous areas. It is believed to be a delayed-type hypersensitivity response to the drug which occurs secondary to systemic absorption of agents after cutaneous sensitization. Our case provides high quality clinical images to aid in clinical diagnosis of this uncommon skin eruption.